Class A dioscorins of various yam species suppress ovalbumin-induced allergic reactions. (June 2014) - Yang, Ching-Chi; Lin, Kuo-Chih
Abstract Context: Dioscorins, the primary storage proteins in yam tubers, of different species exhibited varying immunomodulatory activities in mice. We inferred that this might be attributed to the various isoforms in the yam tubers. Objective: We aimed to investigate the antiallergic potential of the Class A dioscorins of various yam species using the ovalbumin (OVA)-induced murine allergy model. Materials and methods: We purified the recombinant Class A dioscorins (rDioscorins) of various yam species from Escherichia coli and evaluated their antiallergic potential by enzyme-linked immunosorbent assay. Results: The Class A rDioscorins of various yam species suppressed allergic reactions by significantly decreasing the serum IgE and histamine levels. The serum IFN-γ and IgG2a levels significantly increased in all rDioscorin-treated mice. The splenocytes of the rDioscorin-treated mice also exhibited upregulated IFN-γ secretion in response to ConA stimulation. By contrast, the serum IL-5 levels decreased to basal levels in mice treated with Class A rDioscorins and the amount of IL-5 produced by splenocytes decreased in response to ConA stimulation. Discussion: The Class A rDioscorins suppress allergic reactions, possibly through modulating an imbalanced Th1/Th2 immune response to OVA by promoting Th1 cell responses. Furthermore, the Class A rDioscorins of various yam species exhibited similar immunomodulatory activities in OVA-sensitized mice, which were different from the activities demonstrated by native dioscorins, suggesting that distinct immunomodulatory effects of native dioscorins on mice were attributed to the various isoforms in the yam tubers. Conclusion: The Class A dioscorins of various yam species exhibit antiallergic activity and are potential immunotherapeutic agents for treating IgE-mediated hypersensitivity.